Metastatic pulmonary calcification – a case report and review of the literature - Wójcik, Janusz; Grodzki, Tomasz; Kubisa, Bartosz; Pieróg, Jarosław; Piotrowska, Maria; Alchimowicz, Jacek; Wójcik, Norbert (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2012)
We present a case report of a 66-year-old woman with multiple lung nodules up to 1 cm in diameter observed for 2 years. The patient was dialyzed for many years due to end-stage renal failure. No signs of respiratory distress and normal levels of calcium serum were observed. Several individual lung nodules were resected through minithoracotomy and metastatic pulmonary calcification (MPC) was diagnosed. We describe the clinical, morphological and physiological characteristics of MPC and its diagnosis with reference to the present case.